Best Estimate IBNR Reserves in Non-Life Insurance - Proposals for the Calculation of the Solvency II - Jurkiewicz, Tomasz; Pobłocka, Agnieszka (Studia Oeconomica Posnaniensia, 2026)
The European project Solvency II requires the technical provisions (insurance reserves) have to be calculated according to the principle of "best estimate" and increased by the "risk margin". However would such a solution be enough to cover any insurance damage, of which the timing, size and number of insurers are unknown at the time of creating reserves? How in the estimation of reserves to include an assessment of their variation (called volatility). In this paper this problem will be examined in designed simulations. Different proposals for the definitions of the best estimate and the margin of risk incurred through not reported reserves (short IBNR) in non-life insurance will be presented using a variety of deterministic and stochastic methods of estimating these reserves.